Tactical decisions in forensic science: problems, we psychology - Булулуков, О. Ю. (Problems of legality, 2015)
Address the use of psychology in making tactical decisions in the investigation of crimes. Named elements of psychological basis for decision-making and disclosure of their contents. The potential use of psychology developed methods for the selection and decision-making.